Implementation of an assessment system and didactics applying the multiple intelligences theory in the English Class of eleventh graders at Eudoro Granada School (2017)
The present project presents the discoveries of an action research that will be carried out with eleventh graders in a public school in Armenia, Quindío. The objective is improving their proficiency and skills (reading, writing, listening, and speaking) in English by adopting the development of the eight multiple intelligences. Furthermore, this public school requires new techniques and methodology that allow students to develop their potential far from the traditional way (books, photocopies and the little speaker). It showed a big progress by developing their type of intelligence.